Digitalization and the geographies of production: Towards reshoring or global fragmentation?. (April 2021) - Butollo, Florian
The relationship between digitalization and the governance and geographies of global value chains has not been explored systematically. This contribution discusses how digitalization affects the variables that determine the localization of manufacturing, i.e. the substitution of work through automation, the deepening of the customer–producer relationship, the rationalization of distribution through digitalized logistics networks, and the increased modularization of supply chains through standardization and 'platformisation'. The results of the theoretical exploration defy expectations of a straightforward 'reshoring' of production through the combined effects of automation and benefits through a co-localization of companies within their target markets. Tendencies that would support a stronger integration of production in advanced economies are instead being undercut by ongoing countertrends towards fragmentation. The contradictory tendencies of a geographical integration of manufacturing and target markets on the one hand and geographical fragmentation through sophisticated supply-chain organization on the other will affect the technologically facilitated processes of value chain restructuring in a sector-specific manner.